A Study for the Development of a Handbook of Selected Caribbean Herbs for Industry - Seaforth, Compton; Tikasingh, Tricia; Gupta, Mahabir; St Rose, Gilbertha (Technical Centre for Agricultural and Rural Cooperation, 2008)
This study is intended to produce a handbook, for the growers, extension workers, and other partners in the industry. It will provide up-to-date information on twenty Caribbean herbs selected for their possible economic potential...